1988
DOI: 10.1271/bbb1961.52.1541
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic interesterification in supercritical carbon dioxide.

Abstract: An enzymatic reaction with supercritical carbon dioxide (SCCO2) as the reaction medium was investigated. Lipase could catalyze the batch type reaction of hydrolysis and interesterification (acidolysis) in SCCO2at 50°C and 29.4 MPa. The time course of interesterification was influenced by the water content as well as by the kind of reaction medium. The initial velocities of hydrolysis and interesterification were greater in SCCO2than in rc-hexane when the water content increased. A part of this difference in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(33 citation statements)
references
References 2 publications
0
31
0
2
Order By: Relevance
“…This result is also in agreement with works of Marty et al (1990) who reported the stability of lipase in supercritical CO2 under 13 MPa and at 40 'C: a loss of activity of around 10% after 6 days. Effect of Water Content on the Enzymatic Hydrolysis in Supercritical COz: The water content is an important variable, and it can influence the reaction rate (Chi et al, 1988;Marty et al, 1990). Figure 2 shows the effect of water content on the enzymatic hydrolysis in supercritical COa.…”
Section: Resultsmentioning
confidence: 99%
“…This result is also in agreement with works of Marty et al (1990) who reported the stability of lipase in supercritical CO2 under 13 MPa and at 40 'C: a loss of activity of around 10% after 6 days. Effect of Water Content on the Enzymatic Hydrolysis in Supercritical COz: The water content is an important variable, and it can influence the reaction rate (Chi et al, 1988;Marty et al, 1990). Figure 2 shows the effect of water content on the enzymatic hydrolysis in supercritical COa.…”
Section: Resultsmentioning
confidence: 99%
“…This extensive research into these systems has identified and elucidated the effects of many of the important variables, such as pressure (Miller et al, 1990(Miller et al, , 1991Erickson et al, 1990;Ikushima et al, 1993). Reaction rates in SC CO, and in organic solvents (typically hexane) have been compared (Martins et al, 1991;Bolz et al, 1991;Marty et al, 1990Marty et al, , 1992aKamat et al, 1992Kamat et al, , 1993Chi et al, 1988;Pasta et al, 1989). Kinetics parameters and reaction mechanisms have been reported (Miller et al, 1991;Bolz et al, 1991;Marty et al, 1992b;Dumont et al, 1992).…”
Section: Heterogeneous Catalysis and Heterogeneous Reactionsmentioning
confidence: 99%
“…Reported effectiveness factors ranged between 0.36 and 0.60. The water content is an important variable, and it can influence the reaction rate (Miller et al, 1990(Miller et al, , 1991Chi et al, 1988;Marty et al, 1990;Yu et al, 1992;Dumont et al, 1991Dumont et al, , 1992Dumont et al, , 1993Nakamura et al, 1990;Aaltonen and Rantakyla, 1991a). The addition of small amounts of water initially improved the rate because the enzyme requires a microaqueous environment to be active.…”
Section: Heterogeneous Catalysis and Heterogeneous Reactionsmentioning
confidence: 99%
“…Since the first reports on enzyme-catalyzed reactions in supercritical fluids, much attention has been paid to the use of dense gases, mainly supercritical carbon dioxide as potential alternatives to conventional organic solvent ( GARCIA-JUNCEDA et al, 2004;HABULIN;KNEZ, 2001;CHIO;NAKAMURA;YANO, 1988;OLIVEIRA, 2000;OLIVEIRA, 2001). Nevertheless, other compressed gases seem also to be adequate for biocatalysis (HAMMOND et al, 1985).…”
Section: Introductionmentioning
confidence: 99%